Shear strength of cemented soil using triaxial loading - Pan, Huishan (2009)
The study on cemented soil has been increasingly important over the past 2 decades and it had drawn many researchers’ attention about the importance of strength and results of it could help engineers to understand the behavior of the artificial soil so that buildings could be constructed safely on it. Hence the main objective of this report is to study on the shear strength on an artificial soil by conducting undrained and drained triaxial loading tests.